Truth, history and representation in Margaret Atwoods' Alias Grace - Woudstra, Ruth. (University of Cape Town, 2014)
Bibliography: leaves 53. === In the Introduction of this minor dissertation, Margaret Atwood as a post-modern writer and her interest in fictional autobiographies are considered, particularly with regard to memory, the formation of self-identity and amnesia. Parallels are drawn between Surfacing and Cat's Eye as fictional works. and Alias Grace, which is based on the life of a historical person. The novel Alias Grace alternates between first- and third-person accounts, and reflects Atwood's preoccupation with narrative techniques. The definition of post-modernism is regarded, as well as Atwood's own acknowledgements in her ""Author's Afterword"" on how she proceeds to write this fictional autobiography. Her focus on mental illnesses is given perspective in a brief discussion on different sorts of memory loss. These manifestations affect the concept of truth, which is explored in the first section of the dissertation. This section draws on the unreliability of Grace's first-person accounts and the question of whether she is fabricating the truth or has simply forgotten crucial moments of her past. The reader is also constantly made aware that Grace attempts to ensure better conditions for herself in the penitentiary, and she will therefore not disclose any information that might be damaging to her character. That which she discloses partly depends on her relationship in terms of trust with Doctor Jordan. A few episodes where Grace loses consciousness are reviewed, as well as instances where she exposes her literary background and her ability to change words or ideas in texts that she has read. It is concluded at the end of the first section that the truth eludes the reader. With this in mind, it is examined in the second section that the issue of truth is complicated, and even undermined, by the gender and class inequity of the patriarchal society in which Grace, Mary and Nancy are instrumentalised and exploited. The relationship between Grace and Mary is explored in order to demonstrate the happy memories that are relevant in Grace's present, where her past remains illusive. The reader is also drawn into these cheerful experiences, and takes Mary's presence for granted until the neuro-hypnotic seance, during which Grace's double consciousness is revealed. Her 'friend' Mary is exposed as a facet of Grace's own personality. Class oppression is explored further through the characters of Nancy and Mrs Humphrey, who are trapped in a vicious circle that Grace escapes by engaging in the creative activity of quilt-making. In this way she is able to express her solidarity with Mary and Nancy as victims of patriarchal injustice. In the Conclusion an overview of the question of truth is given and it is demonstrated how truth is inseparable from the issues of class and gender relations. The lack of traditional closure in Alias Grace is explored briefly. Grace's camaraderie and solidarity with her two friends, as well as her retelling of the Biblical account of the Garden of Eden through her tapestry work, is shown to be a transgressive agency that marks the greater significance of the novel.